COMPARATIVE CHARACTERISTICS OF THE MORPHOFUNCTIONAL STATE OF STUDENTS IN UNIVERSITIES - Suyundikova, Zh.T.; Pushkova, O. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
omparative characteristics of the morphofunctional state of students in Universities. This article is devoted to comparing the results of a practical study conducted on the basis of the Kostanay State Pedagogical University (KSPU) and the Novosibirsk State Pedagogical University (NSPU), in order to identify differences in morphofunctional indicators between first-year students, depending on gender and place of study. It has been established that students of KSPU, in comparison with students of the NSPU, characterize with low anthropometric parameters, economical consumption of oxygen by the myocardium, higher vital and carpal indices.
Keywords: morphofunctional indicators; health; physical development; sexual differentiation; students